Peculiarity of the low temperature magnetoresistive effect in the Corbino disk with magnetic ordering - Halauchuk, Viktoryia I.; Lukashevich, Michail G. (Journal of the Belarusian State University. Physics, 2021)
The transverse magnetoresistance (MR) hysteresis loops of a magnetically ordered Corbino disk have been studied in the temperature range 300–2 K in an external magnetic field with induction up to 1 T oriented in the plane of the disk (ϕ = 0°) and perpendicularly to its plane (ϕ = 90°). The Corbino disk is made of a thin permalloy film obtained on an insulating sitall substrate by ion-beam sputtering. Independently of the temperature and measurement geometry, the field dependences of MR in the range of weak magnetic fields up to the magnetisation saturation exhibit sharp peaks of the negative MR caused by the domain walls motion during the magnetisation reversal of the sample. The position of the peak in the magnetic field (Bp) is determined by the temperature as well as the angle between magnetic field direction and the disk plane. It was found that a temperature change in the range of T = 300–2 K leads to a change in its position in the range of 0.2–6.0 mT and 8–22 mT at ϕ = 0° and ϕ = 90°, respectively. The magnetic field direction reorientation from in-plane to out-of-pane at T = 2 K leads to the Bp change from 6 to 22 mT. In the range of strong magnetic fields above the magnetization saturation field at ϕ = 0° the positive MR component decreases with induction and has a linear non-saturable dependence down to T ≈ 40–50 K due to the magnon MR component dominance. The complete freezing of magnons at T = 2 K leads to the absence of high-field magnetoresistive effect. At ϕ = 90° in weak fields, the MR changes its sign from positive to negative due to the anisotropic MR component dominance because of the disk magnetisation reorientation perpendicular to the current lines. In a strong field it changes the slope due to the saturation of negative anisotropic MR component, as well as possible additional contribution of the positive geometric Lorentzian MR.
Keywords: permalloy; magnetoresistance; substrate; film; Corbino disk; magnetic ordering